Transfer of a healthy microbiota reduces amyloid and tau pathology in an Alzheimer's disease animal model. Issue 2 (30th August 2019) - Kim, Min-Soo; Kim, Yoonhee; Choi, Hyunjung; Kim, Woojin; Park, Sumyung; Lee, Dongjoon; Kim, Dong Kyu; Kim, Haeng Jun; Choi, Hayoung; Hyun, Dong-Wook; Lee, June-Young; Choi, Eun Young; et al.
Abstract : Objective: Cerebral amyloidosis and severe tauopathy in the brain are key pathological features of Alzheimer's disease (AD). Despite a strong influence of the intestinal microbiota on AD, the causal relationship between the gut microbiota and AD pathophysiology is still elusive. Design: Using a recently developed AD-like pathology with amyloid and neurofibrillary tangles (ADLP APT ) transgenic mouse model of AD, which shows amyloid plaques, neurofibrillary tangles and reactive gliosis in their brains along with memory deficits, we examined the impact of the gut microbiota on AD pathogenesis. Results: Composition of the gut microbiota in ADLP APT mice differed from that of healthy wild-type (WT) mice. Besides, ADLP APT mice showed a loss of epithelial barrier integrity and chronic intestinal and systemic inflammation. Both frequent transfer and transplantation of the faecal microbiota from WT mice into ADLP APT mice ameliorated the formation of amyloid β plaques and neurofibrillary tangles, glial reactivity and cognitive impairment. Additionally, the faecal microbiota transfer reversed abnormalities in the colonic expression of genes related to intestinal macrophage activity and the circulating blood inflammatory monocytes in the ADLP APT recipient mice. Conclusion: These results indicate that microbiota-mediated intestinal and systemic immune aberrations contribute to the pathogenesis of AD in ADLP APT mice, providing new insights into the relationship between the gut (colonic gene expression, gut permeability), blood (blood immune cell population) and brain (pathology) axis and AD (memory deficits). Thus, restoring gut microbial homeostasis may have beneficial effects on AD treatment.